Peran Digitalisasi dan Model Bisnis Dalam Meningkatkan Kinerja Sociopreneurship UMKM Geprek Mira Surabaya - Wira Yudha Alam; Muhammad Zaqhlul Zaidan; Fahrizal Syahrul Huda Bahtiar; Natasya Elok Saputri; Ahmad Naufal Miqdad (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The purpose of this study was to examine how digitalization and business models play a role in improving the performance of Sociopreneurship at the Geprek Mira MSME in Surabaya. The background of the study departs from the challenges faced by MSMEs in Indonesia, namely limited capital, low digital literacy, and limited market access. On the other hand, advances in digital technology and the Sociopreneurship concept provide opportunities for MSMEs to not only focus on economic profits, but also contribute to sustainable social impacts. This study applies a descriptive qualitative approach by collecting data through interviews, observation, and documentation, and using triangulation techniques to ensure data validity. The results show that the use of digitalization techniques through social media, e-commerce, and digital payment systems has succeeded in expanding market reach and increasing operational efficiency of Geprek Mira. On the other hand, an adaptive business model that integrates social missions has succeeded in strengthening the values of sociopreneurship, especially in empowering the surrounding community. The synergy between digitalization and innovative business models has been proven to improve business performance financially, operationally, and socially. Thus, this study confirms that the integration of digital strategies and sociopreneurship-based business models is a key factor for the sustainability of MSMEs in the digital economy era.